Mannheimsia Beyer (Diptera: Phoridae): description of a new species, redescription of Mannheimsia stricta and studies on hypopygial morphology - Ament, Danilo César (Zootaxa, 2012)
Mannheimsia conica, sp. nov., is described, M. stricta redescribed and the hypopygial morphology including the phallus of allfour Mannheimsia species is illustrated and discussed. A table with the different phallus terminology used in the main studies of this structure in Phoridae is presented. Uniformization of phallus terminology is suggested.